2003
DOI: 10.1002/cncr.11531
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term adjustment of survivors of early‐stage breast carcinoma, 20 years after adjuvant chemotherapy

Abstract: BACKGROUND The long‐term impact of breast carcinoma and its treatment was assessed in 153 breast carcinoma survivors previously treated on a Phase III randomized trial (Cancer and Leukemia Group B [CALGB 7581]) a median of 20 years after entry to CALGB 7581. METHODS Survivors were interviewed by telephone using the following standardized measures: Brief Symptom Inventory (BSI), PostTraumatic Stress Disorder Checklist with the trauma defined as survivors' response to having had cancer (PCL‐C), Conditioned Nause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
205
6
18

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 281 publications
(239 citation statements)
references
References 25 publications
10
205
6
18
Order By: Relevance
“…These differences do not appear to be rooted in differences in socioeconomic status (Spencer et al, 1999). Also important in this study, as in that of Kornblith et al (2003), was education level, which presumably relates to income (which was not itself measured). Greater education predicted less frequent financial problems (even in multivariate models), but it also predicted less frequent feelings of having benefited from having had cancer.…”
Section: Long-term Cancer Survivorsmentioning
confidence: 67%
See 1 more Smart Citation
“…These differences do not appear to be rooted in differences in socioeconomic status (Spencer et al, 1999). Also important in this study, as in that of Kornblith et al (2003), was education level, which presumably relates to income (which was not itself measured). Greater education predicted less frequent financial problems (even in multivariate models), but it also predicted less frequent feelings of having benefited from having had cancer.…”
Section: Long-term Cancer Survivorsmentioning
confidence: 67%
“…Ganz et al (2002) found that having had chemotherapy predicted poorer scores at 5-10 year follow-up on a 1-item 'ladder of life,' but not on other measures of mental health (SF-36 mental health index) or depression (the CES-D). Kornblith et al (2003) found that distress 20 years after diagnosis did not relate to medical variables from early in treatment, but it did relate to current interference with functioning due to treatment-related lymphedema and numbness.…”
Section: Introductionmentioning
confidence: 85%
“…Ganz and others 11,12 showed that most women recovered well. Kornblith and colleagues, 13 in a national sample of 15-20 year survivors, showed that women's concerns were no longer related to breast cancer unless they had some persistent problem such as lymphedema. Conversely, both Hodgkin and leukemia survivors 14 and bone marrow transplant patients are apt to have more distress, especially in the presence of physical sequelae and disability.…”
Section: Psychosocial Concerns Of Survivorsmentioning
confidence: 99%
“…Forty-nine percent of the patients (128 of 263) were judged to have SLE. In a 20 year follow-up by Kornblith et al 9 39% of the participants had been diagnosed with SLE. Deo et al 8 followed patients from 1 to 11.5 years and found that 33.5% of patients had clinically significant SLE and that 17.2% had severe SLE.…”
mentioning
confidence: 95%
“…Hinrichs et al 14 found an incidence of 27% for SLE in patients treated with mastectomy followed by radiotherapy. In these four studies, SLE was determined using patient self-report and self-circumferential measurement, 13 patient self-report, 9 serial circumferential measurement method, 8 and chart review. 14 In contrast to this research, current reports of incidence with SNLB has been 0 -23%.…”
mentioning
confidence: 99%